Learning to pull the strings after Suez: Macmillan’s management of the Eisenhower administration during the intervention in Jordan, 1958 - Kettle, Louise (Routledge, 2016)
This analysis re-instates the importance of the 1958 British intervention in Jordan within the study of Anglo-American relations and the revisionist literature on Suez. It does so by challenging the idea of British subservience to American foreign policy after the 1956 crisis, and it reveals two key lessons learnt by London: that Britain’s economy, power, and influence were in decline and that Britain could no longer intervene in the Middle East without American support. Having learnt these lessons, Prime Minister Harold Macmillan proved to be a shrewd political actor who used the opportunity of the Jordan intervention to turn the policy of the Dwight Eisenhower Administration to British ends, regaining Britain’s maximum power and prestige for the minimum loss of resources.